2017
DOI: 10.1097/icl.0000000000000284
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of an Artificial Tear Containing 0.3% Hyaluronic Acid in the Management of Moderate-to-Severe Dry Eye Disease

Abstract: Visaid 0.3% is a safe product with some benefits over 0.9% NaCl in reducing ocular symptoms and improving some ocular signs in patients with moderate-to-severe dry eye.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 33 publications
3
30
0
Order By: Relevance
“…While earlier studies have measured and compared tear meniscus height using the Schirmer test and anterior segment swept-source optical coherence tomography, 12,13 the measurement of this parameter with the Keratograph exhibits high reliability and repeatability. 14 In our study, we observed a significant increase in tear meniscus height at 1 week and 1 month. Traditionally, conjunctival hyperemia is assessed using visual scales, 15 which are subjective, while the analysis of conjunctival hyperemia using the Keratograph, is a quick and easy process.…”
Section: Discussionsupporting
confidence: 56%
“…While earlier studies have measured and compared tear meniscus height using the Schirmer test and anterior segment swept-source optical coherence tomography, 12,13 the measurement of this parameter with the Keratograph exhibits high reliability and repeatability. 14 In our study, we observed a significant increase in tear meniscus height at 1 week and 1 month. Traditionally, conjunctival hyperemia is assessed using visual scales, 15 which are subjective, while the analysis of conjunctival hyperemia using the Keratograph, is a quick and easy process.…”
Section: Discussionsupporting
confidence: 56%
“…These results coincided with previous researchers [31][32][33] who confirmed that, SH acts as a tissue lubricant through its high viscosity that modulates the interactions between neighboring tissues and provides mechanical protection of corneal epithelium and endothelium. Moreover, lubricating topical SH eye drops promoted water retention on corneal surface, accelerated corneal wettability and extended the time of drug contact with cornea so; it enhanced drug bioavailability and protected ocular surface epithelium by facilitating corneal epithelial healing [34] .…”
Section: Discussionsupporting
confidence: 92%
“…Gel eye drops do not allow accurate and reproducible drug administration and can cause blurred vision, crusting on the eyelids, and tearing [9][10][11]. In general, these formulations consist of cellulose derivatives, such as carboxymethylcellulose (CMC) [12,13], hydroxypropylmethylcellulose (HPMC) [14,15], carbomer (carbopol), or hyaluronic acid (HA) [16][17][18]. Cellulose derivatives were the first polymeric materials to be applied as excipients in ophthalmic pharmaceutical forms [19].…”
Section: Gel Eye Dropsmentioning
confidence: 99%